2007
DOI: 10.1007/s11182-007-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of dielectric properties in a polycrystalline lithium-titanium ferrite

Abstract: A. V. Malyshev and V. V. Peshev UDC 537.226 For the first time a dielectric hysteresis is observed in a polycrystalline lithium-titanium ferrite in the temperature range 475-575 K. A thermal Barkhausen effect is detected during heating and cooling of ferrite specimens prepolarized in an electric field. The results provide evidence on the formation of properties similar to ferroelectric ones in lithium-titanium ferrites under certain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The technology of sample sintering and preparation was the same as in [2]. The samples were prepared using the conventional ceramic technology from industrially synthesized 3SCh-18 sort charge by thermal sintering of compacts in air in a laboratory resistance furnace under the following technological conditions: sintering temperature T sint = 1283 K and sintering time t sint = 2 h. The chosen sintering conditions corresponded to the technology of industrial sintering of ferrite ceramics of this sort.…”
Section: Technology Of Sample Preparation and Their Investigation Promentioning
confidence: 99%
See 1 more Smart Citation
“…The technology of sample sintering and preparation was the same as in [2]. The samples were prepared using the conventional ceramic technology from industrially synthesized 3SCh-18 sort charge by thermal sintering of compacts in air in a laboratory resistance furnace under the following technological conditions: sintering temperature T sint = 1283 K and sintering time t sint = 2 h. The chosen sintering conditions corresponded to the technology of industrial sintering of ferrite ceramics of this sort.…”
Section: Technology Of Sample Preparation and Their Investigation Promentioning
confidence: 99%
“…This search is of doubtless interest from the practical and fundamental viewpoints [1]. In [2,3] it has been demonstrated that under certain conditions, Li 0.649 Fe 1.598 Ti 0.5 Zn 0.2 Mn 0.051 O 4 ceramics shows the dielectric characteristics typical of the ferroelectric materials. Namely, anomalously high values of the real component of the complex dielectric permittivity ε′ ≈ 10 3 were established (at a frequency of 100 Hz and ferrite temperature of 400 K) with a sharp decrease in ε′ upon heating of the samples to temperatures of the order of 550 K together with the abrupt changes in the temperature dependence of ε′ measured in a constant bias electric field.…”
Section: Introductionmentioning
confidence: 99%